Assessment of the Effectiveness of Matrix Model Among Methadone Patients Using ATS in Ho Chi Minh City, Vietnam - Han Dinh Hoe; Khoa Tran; Nguyen Van Hai; Pham Thi Huyen Trang; Nguyen Thi Lien (Newinera Publisher, 2021)
This study assessed the effectiveness of the application of the Matrix model in patients undergoing methadone treatment for Amphetamine-type substance (ATS) in Ho Chi Minh City. A total of 951 methadone patients were screened; 60 (16%) met the inclusion criteria and of those 51 (85%) completed 16 weeks of study procedures. Most of the participants were ATS users with moderate or higher risk of dependence. Compared to the non-intervention group, the intervention group showed a significant reduction in positive urine tests for methamphetamine (a decrease from 100% to 11% vs. a decrease from 100% to 98% for the non-intervention group, p<0.001) and for opiates (a decrease from 36.7% to 3.7% vs. a decrease from 43.3% to 29.2% for the non-intervention group). In the intervention group, the quality of life increased from 76.74 points to 85.5, the proportion of depression decreased from 43.3% to 18.5%, anxiety decreased from 30% to 11.1%, and stress decreased from 76.7% to 29.6%. In the non-intervention group, quality of life decreased from 75.2 points to 74.5 points, the proportion of depression decreased slightly from 40% to 36%, anxiety decreased from 33.3% to 24%, and stress decreased from 76.7% to 76.0%. The intervention group was significantly more likely to adhere to methadone treatment (p<0.001). The proportions of participants in the intervention group and non-intervention group who discontinued treatment were 10% and 20%, respectively. The study results suggested that the MATRIX model could help reduce ATS and opiate use and improve mental health as well as treatment adherence.